Pemanfaatan Struktur dan Aspek Kebahasaan Teks Pidato Tokoh-Tokoh Nasional Sebagai Bahan Ajar Digital - Ade Nuryadin; Suherli Kusmana; Jaja Jaja (Anufa Ikaprobsi, 2023)
This study aims to overcome the difficulty of obtaining teaching materials that are in accordance with the development of information technology, in the form of digital speech text teaching materials for SMP/MTs students. Speech is an activity that shows a language skill that is needed by students as provision in their lives in society. Therefore, the development of speech text teaching materials is suitable to be implemented as teaching materials. This study uses a research and development method that begins by analyzing speech activities carried out by national figures classified into three categories (officials, political party figures, and religious leaders) contained in Google's electronic media (youtube). The structure and language features of the speech text were analyzed qualitatively descriptively to find out the contents of the speech text based on the appropriate structure and content categories. Selected speech texts are applied as teaching materials which are developed and the use of language is adapted according to curriculum indicators. The validation instrument consists of four aspects of assessment, namely content feasibility, language, presentation, and graphics. Based on the validity test by experts and practitioners it is known that the digital teaching materials developed are valid and can be used. Based on the results of implementation in learning, YouTube-based digital teaching materials, speech text materials processed based on the t-test, it can be stated that the teaching materials are effective. The response of students in learning was very enthusiastic, both in watching and imitating speeches in front of the class, and learning to write speech texts, so that learning outcomes were considered effective. Penelitian ini bertujuan untuk mengatasi kesulitan mendapatkan bahan ajar yang sesuai dengan perkembangan teknologi informasi, berupa bahan ajar teks pidato digital bagi siswa SMP/MTs. Pidato merupakan kegiatan yang menunjukkan suatu keterampilan berbahasa yang diperlukan siswa sebagai bekal dalam kehidupannya di masyarakat. Oleh karena itu, pengembangan bahan ajar teks pidato cocok untuk diimplementasikan sebagai bahan pengajaran. Penelitian ini menggunakan metode penelitian dan pengembangan yang dimulai dengan menganalisis kegiatan berpidato yang dilakukan oleh tokoh-tokoh nasional yang diklasifikasikan ke dalam tiga kategori (pejabat, tokoh partai politik, dan pemuka agama) yang terdapat dalam media elektronik google (youtube). Struktur dan ciri kebahasaan teks pidato dianalisis secara kualitatif deskriptif untuk mengetahui isi teks pidato berdasarkan kategori struktur dan isi yang sesuai. Teks pidato terpilih diterapkan sebagai bahan ajar yang dikembangkan dan penggunaan bahasa diadaptasi sesuai dengan indikator kurikulum. Instrumen validasi terdiri atas empat aspek penilaian, yaitu kelayakan isi, bahasa, penyajian, dan kegrafikaan. Berdasarkan uji validitas oleh ahli dan praktisi diketahui bahwa bahan ajar digital yang dikembangkan valid dan dapat digunakan. Berdasarkan hasil implementasi dalam pembelajaran, bahan ajar digital berbasis youtube materi teks pidato yang diolah berdasarkan uji-t dapat dinyatakan bahwa bahan ajar tersebut efektif. Respon siswa dalam pembelajaran sangat antusias, baik dalam memirsa maupun menirukan berpidato di depan kelas, serta belajar menulis teks pidato, sehingga hasil pembelajaran termasuk efektif.